Introduction to recreation services for people with disabilities a person-centered approach - Bullock, Charles C; Mahon, Michael J. (Urbana, IL Sagamore Publishing, 2016)
Introduction to recreation services for people with disabilities continues to reflect a broad-based explanation of the role of practitioners in the interrelated fields of therapeutic recreation, inclusive recreation, and special recreation. This fourth edition represents a major revision, including the most current research and thinking about the interdisciplinary fields of recreation and disability studies. This book is intended to be an introductory text for all students in parks and recreation/leisure studies departments. Every student, whether she or he intends to work in a provincial park or a state hospital, a community recreation center or a community mental health center, a public school or a cruise ship, needs a basic level of knowledge about people with disabilities. The central theme of this book is that people with disabilities are people who have the same needs and wants as anyone else and deserve the right to be at the center of their services. Each person with a disability is a person first, not a disability. Recreation services must be centered around the person who is being served. That is, whether treatment-oriented recreation therapy, goal-oriented special recreation, or activity-oriented inclusive recreation, it is the person and not the professional or even the activity that must be at the center of service delivery
1. Who are people with disabilities? -- 2. History of treatment of people with disability -- 3. Conceptual cornerstones of service delivery -- 4. Legislation related to people with disabilities and recreation -- 5. Discrimination, barriers, and accessibility -- 6. Special recreation, inclusive recreation, and therapeutic recreation programs for people with disabilities: an overview -- 7. Cross Disability topics -- 8. People with intellectual and developmental disabilities -- 9. People with physical disabilities -- 10. People with visual impairments -- 11. People with hearing loss -- 12. People with mental illness -- 13. Inclusive recreation -- 14. Therapeutic recreation: the profession of therapeutic recreation, the practice of recreational therapy -- 15. Leisure education -- 16. Sport and people with disabilities -- 17. How do I stay current?